Assessment and genetic improvement of aluminium tolerance in South African winter bread wheat cultivars - Motupa, Mamotlole Patricia (University of the Free State, 2010)
This study was undertaken to evaluate 11 wheat genotypes for aluminium tolerance using three laboratory based evaluation methods. Four parameters namely the root length before aluminium treatment, the root re-growth after aluminium treatment, the portion of the root affected by aluminium treatment, stained with hematoxylin and root tolerance index were measured on the two longest (primary and secondary) roots of each seedling to determine the effect of aluminium toxicity on the physiological development of the seedling roots. With the root re-growth method it was possible to distinguish between three categories of tolerance (moderate, intermediate and tolerant) that will be very helpful in future resistance breeding for aluminium tolerance. With this method it is possible to discriminate between individuals in a population for aluminium tolerance. Similar data was obtained for the primary and secondary roots, which indicated that the age of the roots are not a limiting factor for aluminium tolerance screening with the nutrient bioassay. Although the root re-growth method discriminated between the different aluminium tolerance categories, a better indication of aluminium tolerance categories was achieved with the root tolerance index method. With the above methodology in place it was possible to observe an increase in aluminium tolerance in some progeny after gene recombination and it was possible to discriminate between good aluminium tolerant progeny and progeny showing no genetic gain from the hybridisation. It was also shown that there were no reciprocal effects for aluminium tolerance in wheat. There were genetic differences for aluminium tolerance between the genotypes used in this study and this methodology can be successfully implemented in an aluminium tolerance-breeding programme for wheat. This study indicated that there is useful methodology to effectively follow the genetic gains during gene-recombination for aluminium tolerance and, secondly that there are different genetic resources available in wheat that can be utilised to increase aluminium tolerance.

Hierdie studie is onderneem om 11 koring genotipes te evalueer vir aluminium toleransie met die gebruik van drie laboratorium gebaseerde evaluasie metodes. Vier parameters naamlik die wortellengte voor aluminium behandeling, die hergroei na aluminium behandeling, die gedeelte van die wortel wat deur aluminium behandeling beïnvloed is en gekleur is met hematoksilien en wortel toleransie indeks wat gemeet is op die twee langste (primêre en sekondêre) wortels van elke saailing, is gebruik om die effek van aluminium toksisiteit op elke saailing se fisiologiese ontwikkeling van hulle wortels te bepaal. Dit was moontlik om te onderskei tussen drie kategorië van toleransie (laag, intermediêr en tolerant) met die wortel hergroei metode. Dit sal baie nuttig wees vir toekomstige weerstandsteling vir aluminium toleransie. Met hierdie metode was dit moontlik om tussen individue te onderskei vir aluminium toleransie binne ‘n populasie. Die data vir primêre en sekondêre wortels was baie dieselfde, wat aandui dat die ouderdom van die wortels nie ‘n beperkende faktor is wanneer daar met die voedings biotoets vir aluminium toleransie getoets word met nie. Alhoewel die wortel hergroei metode onderskei het tussen verskillende aluminium toleransie kategorië, is ‘n beter aanduiding van aluminium toleransie verkry met die wortel toleransie indeks metode. Met bogenoemde metodes was dit moontlik om die toename van aluminium toleransie in die nageslag te sien na kruisings en dit was moontlik om te onderskei tussen nageslag met goeie toleransie, en die wat geen genetiese verbetering na gee-herkombinering getoon het nie. Daar is ook gewys dat daar geen resiproke effekte vir aluminium toleransie in koring is nie. Daar was genetiese verskille vir aluminium toleransie tussen die genotipes wat gebruik is in hierdie studie en hierdie metodes kan dus suksesvol gebruik word in ‘n aluminium toleransie teelprogram vir koring. Die metodes is dus beskikbaar om genetiese verbetering in toleransie te volg na kruisings vir aluminium toleransie en tweedens is die genetiese bronne beskikbaar in koring wat gebruik kan word om aluminium toleransie te verbeter.
Dissertation (M.Sc. (Plant Sciences: Plant Breeding))--University of the Free State, 2012
Keywords: Winter wheat -- Genetics; Winter wheat -- Fertilizers